Review of Chinese species of the genus Denierella Kaszab with a key to the worldwide species (Coleoptera, Meloidae) - Yang, Yu-Xia; Ren, Guo-Dong (Zootaxa, 2007)
The Oriental genus Denierella Kaszab is reviewed with description of a new species, D. striolata sp. nov., from Yunnan Province and re-description of two other Chinese species. A key to the world species of this genus is provided.